O sábado no Antigo Testamento e na perspectiva de Jesus - Wilhelm, Fabio (2014)
This study aims to investigate the Sabbath in the Bible and the implications that it has brought to the people of God. Also, we will study Jesus´s position regarding the Sabbath. The first chapter explores the Sabbath in the Old Testament period, in order to understand the value of this institution in the times of Jesus. In the second chapter, we will do an exegesis of the Gospel of Mark (2:23-28), in which a discussion between Jesus and the Pharisees about the Sabbath is reported. The conflicts of Jesus, in the Gospels, regarding the Sabbath revolve almost solely around what things were allowed to do or not allowed to do on that day. All texts deal with cures on the Sabbath, with the exception of Mark 2:23-28. We will analyze the position of Jesus in relation to the Sabbath, based on this pericope, for Jesus establishes this one as the primary matrix for understanding all the other texts on the Sabbath. We finish by presenting the advent of Sunday as the day to commemorate the resurrection of Jesus. The day of the resurrection became special for the memory of the first Christians and for the Christian Church.